Triglyceride-Rich Lipoproteins: Their Role in Atherosclerosis - Yulino Castillo-Núñez; Enrique Morales-Villegas; Carlos A. Aguilar-Salinas (Permanyer, 2022)
The term "triglyceride-rich lipoproteins" (TRLs) includes chylomicrons and their remnants, very low-density lipoproteins (VLDL), and intermediate-density lipoproteins (IDL). In this manuscript, the mechanisms by which atherogenic TRLs contribute to the formation of atheroma plaques are reviewed. Cholesterol from TRLs that can be retained in the subendothelial space (i.e., remnants, DLs, and small VLDLs) contributes to the genesis of atherosclerosis. Triglycerides of atherogenic TRLs induce inflammation of the arterial wall. Mechanisms that explain the involvement of TRLs in atherosclerosis are the generation of pro-atherogenic changes in high-density lipoproteins and low-density lipoproteins, accumulation of TRLs in plasma, and their passage to the subendothelial space where they cause endothelial dysfunction and inflammation of the vascular wall. Furthermore, plasma accumulation of TRLs causes hyperviscosity and a procoagulant state. Finally, this manuscript summarizes the controversial aspects of the clinical approach and the treatment of cases with dyslipidemia explained by atherogenic TRLs.